2019
DOI: 10.1038/s41598-019-43768-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination and analysis of agonist and antagonist potential of naturally occurring flavonoids for estrogen receptor (ERα) by various parameters and molecular modelling approach

Abstract: Most estrogen receptor α (ERα) ligands target the ligand binding domain (LBD). Agonist 17β-estradiol (E 2 ) and tamoxifen (TM, known SERM), bind to the same site within the LBD. However, structures of ligand-bound complexes show that E 2 and TM induce different conformations of helix 12 (H12). During the molecular modelling studies of some naturally occurring flavonoids such as quercetin, luteolin, myricetin, kaempferol, naringin, hesperidin, galangin, baicalein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…Molecular docking on GPER structures extracted from all-atom MD has demonstrated ( 48 ) that the natural polyphenol (–)-epicatechin (see Figure 2 ) has the ability to anchor to this receptor with a binding mode similar to the agonist G-1. It is interesting to note that flavonoids sharing structural similarities to estrogens, such as genistein and other phytoestrogens ( 49 51 ), not only bind but also activate the classical receptors ERα and ERβ. In contrast, and in spite of its evident structural analogies to these phytochemicals, (–)-epicatechin fails to bind ERα and ERβ.…”
Section: The Current Area Of Computational Methods For Studying Gpermentioning
confidence: 99%
“…Molecular docking on GPER structures extracted from all-atom MD has demonstrated ( 48 ) that the natural polyphenol (–)-epicatechin (see Figure 2 ) has the ability to anchor to this receptor with a binding mode similar to the agonist G-1. It is interesting to note that flavonoids sharing structural similarities to estrogens, such as genistein and other phytoestrogens ( 49 51 ), not only bind but also activate the classical receptors ERα and ERβ. In contrast, and in spite of its evident structural analogies to these phytochemicals, (–)-epicatechin fails to bind ERα and ERβ.…”
Section: The Current Area Of Computational Methods For Studying Gpermentioning
confidence: 99%
“…This protective associations could be explained by the ability of some polyphenol subclasses to generate similar responses to estrogen (phytoestrogens), as their structure resembles the most important type of estrogen in humans and possesses hydroxyl groups and phenolic rings, necessary for binding to estrogen receptors [46]. In addition, several studies reported that some of the estrogen receptor (ER)-mediated responses induced by flavonoids are comparable, or even superior, to those induced by physiological levels of estradiol [47].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the same signaling pathways are regulated by CYP450–estradiol interactions, and there are plenty of data available on this topic. Moreover, other calculation methods are also applied, including ADMET and molecular dynamics (MD) [ 90 , 91 ] (for MD description and examples, see Section 2.1.3 ). Nowadays, in silico methods are a standard tool in plant xenoestrogens studies.…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%